A Comparison of Barbed Suture Versus Traditional Techniques for Muscle Belly Repair. (January 2019) - Goyal, Kanu S.; Speeckaert, Amy L.; Goitz, Robert J.; Tavana, M. Lance
Background: The use of barbed sutures in wound closure and tendon repair has been previously been studied with improved results over traditional suture material. We examine the use of barbed suture in muscle belly repair in a custom configuration, comparing it with traditional configurations and a control.Methods: Twenty-five matched porcine psoas muscles were assigned to 5 different test groups: Mason-Allen with #1 Ethibond, Figure of Eight Allen with #1 Ethibond, Modified Kessler with #1 Ethibond, Custom Configuration with #2 Barbed PDS, Custom Configuration with #1 Ethibond. Repair was performed on the cut edge of muscle, with the free end of the suture anchored to a fixed base, forming a single-sided repair. An Instron 8874 tensiometer was used to linearly distract the repair to failure at 1 mm/s after 1 N preload. Five samples of each group were run, comparing load to failure and distraction at 10 N.Results: Repair with barbed suture in custom configuration had statistically significantly greater load to failure than all other methods. It also showed statistically significant less displacement at 10 N of force than all other methods of repair except the Mason-Allen repair with #1 Ethibond. Mode of failure for traditional techniques was suture pull-through with tissue loss. Failure with barbed suture was through suture pullout without tissue loss.Conclusions: Custom configuration with a barbed suture increases the load to failure and decreases displacement of the repair site at 10 N of force. In addition, when the suture does pull out, it does so with minimal tissue loss.